Antecedents of Citation Impact and Intention to Publish on Open Access Journals: A Case of Agricultural Research Institutes Tanzania - Massoro, Zainabu Zuberi; Othman, Roslina (International Journal of Emerging Trends in Social Sciences, 2018)
This study assessed the factors that contribute to intention to publish in open access journals among researchers in Tanzanian Agricultural Research Institutes. Five factors derived from the literature were used to predict intention to publish in Open Access Journals. These factors are: journal reputation, the speed of publishing, content relevance, visible advantage and citation impact. Data were collected from 121 researchers through a cross-section survey questionnaire. The findings revealed that journal reputation, visibility advantage and citation impact have significant effect on intention to publish in open access journals. Nonetheless, further analysis showed that the speed of publishing as well as content relevance have no significant influence on citation impact. This article articulates the basis for research institutions and practitioners to nurture open access publishing in order to address the dearth of empirical studies on open access journal publishing in Tanzania.